Teaching Method As Capital In Information Exchange Activities - Rivaldy Hermawan, Muhammad (Devotion : Journal of Research and Community Service, 2022)
Teaching methods can be adapted to the type of activity carried out and also adapted to the subjects being taught. Basically deciding on a teaching method in a teaching activity is very difficult to determine and it is impossible to apply only one method, it is possible that there will be collaboration between teaching methods so that they can complement each other. With the hope that the learning and teaching process goes well and can be accepted by students. This study aims to determine and analyze the use of learning methods in an effort to increase student learning outcomes to the maximum in teaching and learning activities. This study uses both quantitative and qualitative research data obtained from various journals. The research method in this article uses a systematic literature review approach adopted from Keathley and Van Aken (2013). The stages of literature review are carried out through several stages, namely article selection, article review, and analysis of findings. The results of the study explain that the methods that can be used in learning activities that can be understood by students must be based on the strengths and weaknesses of students. Teachers are required to meet these deficiencies from each student such as developing learning programs, using assistive media that can stimulate students to actively participate in teaching and learning activities. From this research it can be found that the importance of implementing appropriate and effective methods is an obligation. With the hope that learning activities will run as planned and not deadlocked. Therefore, some methods of teaching and learning activities that are deemed appropriate and effective may be applied in the actual learning process.